PREDIKTOR SIKAP STIGMA DAN DISKRIMINASI TERHADAP ORANG DENGAN HIV DAN AIDS (ODHA) DI KABUPATEN JEMBER - Ni’mal Baroya (Jurnal Ilmu Kesehatan Masyarakat, 2017)
Globally, the HIV and AIDS epidemic shows stable conditions, but statistically there is still an increase in new infections in some areas including Jember District. The main barriers to HIV prevention are stigma and discrimination against people living with HIV. This study aims to analyze the predictors of stigma and discrimination attitude toward PLHIV in Jember District. This was an observational study used cross sectional design. Research subjects were people aged 15-24 years amounted to 247 respondents. Determination of the sample using a multistage sampling technique, ie the determination of simple random cluster of villages and then determine the respondents of each cluster randomly systematic. Data were collected using structured interview technique with questionnaire then analyzed using chi-square test and logistic regression with 5% significance level. The results showed the majority of respondents (81.4%) stated not willing to buy food if the seller knew HIV +. Fifty percent more they disagree if female teachers who are HIV + keep teaching. Similarly, children with HIV + cannot be admitted to school with HIV negative children. The distribution of stigma and discrimination attitudes toward people living with HIV significantly differed by age, sex, education level, marital status and occupational status. The level of knowledge and residence does not differ significantly. A significant factor to be a predictor of stigma and discrimination against people living with HIV is age and gender. Younger age (15-19 years) and women have a greater likelihood of being stigmatized and discriminating against people living with HIV. Dissemination of information about HIV and AIDS in adolescents aged 15-19 years is still needed to increase knowledge and accelerate the acceptance of PLHIV so that stigma and discrimination attitude toward PLWHA can be reduced. Keywords: attitude, stigma, discrimination people suffering with HIV and AIDS.